Peningkatan Laju Pelarutan Celecoxib Menggunakan Dispersi Padat dengan Polimer HPMC yang Dikombinasi PVP dan PEG 6000 - Danang Novianto Wibowo; Anita Sukmawati (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Celecoxib has poor solubility and categorized as Biopharmaceutical Classification System (BCS) class II drug therefore, it prepared into the solid dispersion system in order to enhance drug solubility. This study aims to determine physical characteristic and the dissolution rate of celecoxib in solid dispersion systems using Hydroxypropyl methylcellulose (HPMC) polymers combined with polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG) 6000. Celecoxib solid dispersions (CSDs) were prepared with HPMC-PVP in ratio of 1:2 and 2:1 and HPMC-PEG 6000 in ratio 1:2 and 2:1. The dissolution rate of CSDs were evaluated using dissolution method and physical characteristics were evaluated using the X-ray Powder Diffraction (XRPD). The result showed that the CSD containing HPMC-PVP 1:2 as a matrix had the highest dissolution rate (0.808 mg/cm2/minute). The dissolution rate was higher than pure celecoxib (0.400 mg / cm2 / minute). The characterisation of the crystalline degree of celecoxib solid dispersions (CSDs) using the X-ray Diffraction showed a decrease in the peak intensity of the interferance of the crystalline phase. The solid dispersion system using HPMC-PVP 1:2 could enhance the rate of dissolution of celecoxib twice highest than pure celecoxib. The highest dissolution rate value was found in celecoxib solid dispersion with 1:2 HPMC-PVP as a matrix.